2019
DOI: 10.3389/fnut.2019.00046
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ketone and Medium Chain Fatty Acid Response in Humans Consuming Different Medium Chain Triglycerides During a Metabolic Study Day

Abstract: Background: Medium chain triglycerides (MCT) are ketogenic but the relationship between the change in plasma ketones and the change plasma medium chain fatty acids (MCFA)—octanoate, decanoate, or dodecanoate—after an oral dose of MCT is not well-known. An 8 h metabolic study day is a suitable model to assess the acute effects on plasma ketones and MCFA after a dose of tricaprylin (C8), tricaprin (C10), trilaurin (C12) or mixed MCT (C8C10). Objective: To assess in healthy huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 29 publications
3
65
2
Order By: Relevance
“…Our results are in line with previous findings on changes in ketosis after intake of different fatty acids (11,12), but adds information on their relative contribution in relation to fasting ketosis, and also expands the evidence to include an older sample. Extension of the non-carbohydrate window of an overnight fast-by replacing breakfast with coffee plus any of the tested fatty acids-induced a mild ketosis in the same range as the additional effect of 20 g C8 (on AUC/time).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results are in line with previous findings on changes in ketosis after intake of different fatty acids (11,12), but adds information on their relative contribution in relation to fasting ketosis, and also expands the evidence to include an older sample. Extension of the non-carbohydrate window of an overnight fast-by replacing breakfast with coffee plus any of the tested fatty acids-induced a mild ketosis in the same range as the additional effect of 20 g C8 (on AUC/time).…”
Section: Discussionsupporting
confidence: 91%
“…Another strength of our study is the complete collection of rich data, assessed under well-controlled conditions. Previous studies (11,12) have reported that coconut oil, C12 and C8 were associated with different ratios between the two blood ketones BHB and AcAc, raising interesting questions on potential variations in their metabolism. If such a difference is present, interpretations may be biased when only BHB is used to assess ketosis, as for the primary outcome of our study.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, the main medium-chain triglyceride constituent in coconut oil is dodecanoic acid (lauric acid, C12), with decanoic acid (capric acid, C10) and octanoic acid (caprylic acid, C8) as the great remainder (100). When given in equal amounts, intake of decanoic acid and octanoic acid leads to a greater ketone production postprandially then dodecanoic acid (101,102). Thus, to increase the effect of medium-chain triglycerides on ketogenesis, a concentrated oil with a higher quantity of decanoic and octanoic acid can be given instead of coconut oil.…”
Section: Limitationsmentioning
confidence: 99%